“This pen is more important than this firearm”: Exploring security sector governance in South Africa during the COVID-19 pandemic - Michaels, Gino Stephano (Department of Public Law, 2025)
This dissertation critically explores the nature of Security Sector Governance (SSG) in South Africa during the COVID-19 pandemic, focusing specifically on the roles, responsibilities, experiences, and perceptions of members of the South African Police Service (SAPS). Set against the backdrop of an unprecedented public health crisis, the research examines how a highly securitised approach—underpinned by the Disaster Management Act—shaped the implementation of pandemic-related policies. Using a qualitative, single-case study design centered on Kraaifontein Police Station, the study engages with ten SAPS officers through semi-structured interviews, complemented by insights from a Community Policing Forum chairperson and a policing scholar. The findings reveal a fragmented security governance landscape, marked by overlapping institutional frameworks, contested governance, and a blurring of public health and public safety roles. SAPS officers were often unprepared for the public health dimensions of their expanded mandates and struggled with inadequate training, limited personal protective equipment, and heightened exposure to psychological stress. Officers' responses highlight the tension between duty and vulnerability, militarised policing tactics, and the shifting legitimacy of state authority. Drawing from the Mo Ibrahim Index of African Governance, the study evaluates governance performance across indicators such as rule of law, accountability, and security provision. Ultimately, the research underscores the limitations of a militarised pandemic response in a fragile state context and calls for a more inclusive, community-oriented, and health-integrated approach to security governance during states of emergency. Recommendations include structural reforms in inter-agency collaboration, police training, and community engagement to enhance transparency, resilience, and trust within the security sector